Analysis of Metabolites Difference of the Albino Tea Tree Variety 'Ming Guan' - Xiaomei YOU; Aodi HAN; Xinlei LI; Xiangrui KONG; Sitong ZHONG; Yuqiong GUO; Ruiyang SHAN; Changsong CHEN (Shipin gongye ke-ji, 2023)
‘Ming guan’ is a new excellent albino tea variety bred from the descendants of Bai jiguan. In order to explore the quality difference of Ming guan multi tea processing, the fresh leaves of Ming guan were used as raw materials to make the corresponding tea types according to the processing methods of green tea, black tea and white tea, and sensory quality evaluation, aroma and taste analysis were conducted. The results showed that the aroma of Ming guan green tea was tender, floral and fruity, with a mellow taste, the aroma of Ming guan black tea was sweet, floral, with a sweet taste, the aroma of Ming guan white tea was millets, floral, with a fresh taste, and the different processes of Ming guan tea had their own unique floral characteristics. Among the aroma components of Ming guan green tea, terpene aroma components with floral aroma were relatively more abundant, followed by ester aroma components with fruit aroma, which played an important role in the formation of the aroma of Ming guan green tea. The representative aroma components of Ming guan green tea were leaf alcohol ester of foliol caproate, 3-hexenyl caproate, 2-hexenyl caproate, nerolidol, leaf alcohol ester of butyric acid, olivetol and α-farnesene, the representative components of which were mainly esters with fruity aroma and alcohols with floral and fruity aroma, creating the characteristic of Ming guan green tea floral and fruity varieties. The representative components of Ming guan black tea were dihydrolinalool, α-cephalene, β-Ionone, γ-cadinene, methyl hexadecanoic acid and benzaldehyde, which were mainly terpenes and alcohols with floral and sweet aromas, contributing to the floral and sweet aromatic characteristics of Ming guan black tea. The representative components of Ming guan white tea were geraniol, myrcene, 3-carene, linalyl acetate and linalool, and the representative components are mainly alcohols and terpenes with floral aroma. The non-volatile components of Ming guan green tea, Ming guan black tea and Ming guan white tea vary greatly overall. The content of catechins, anthocyanins, some flavonols and flavonoid glycosides (quercetin-3-O-galactoside, quercetin-3-O-glucoside, quercetin-3-O-glucoside 7-O-rhamnoside, etc.) in Ming guan green tea was generally higher than that in Ming guan black tea and Ming guan white tea. The contents of theaflavins, phenolic acids, a few flavonol and flavonoid glycoside compounds (vitexin-2-O-galactoside, vitexin-2-O-rhamnoside, apigenin-6,8-di-C-glucoside, apigenin-6-C-glucoside, etc.) and some amino acid compounds (L-phenylalanine, L-tryptophan, L-isoleucine, L-valine, L-aspartic acid) in Ming guan black tea were higher than those in Ming guan green tea and Ming guan white tea.The content of some amino acid compounds (L-arginine, L-glutamine, L-lysine, L-histidine, L-tyrosine) in Ming guan white tea was higher than that in Ming guan green tea and Ming guan black tea, which may be affected by different processing technologies. This study could provide a theoretical basis for a comprehensive understanding of the chemical basis and quality differences of Ming guan green tea, Ming guan black tea and Ming guan white tea.